Comparison of the efficacy of budesonide by nebulizer, metered dose inhaler and dry powder inhaler in chronic stable bronchial asthma - Rizvi, Dilshad Ali; Abidi, Afroz; Agarwal, Abhishek; Ahmad, Ali (International Journal of Basic & Clinical Pharmacology, 2018)
Background: The study has been performed to evaluate the efficacy of budesonide delivery by different form of devices like nebulizer, metered dose inhaler and dry powder inhaler to adult patients of chronic stable bronchial asthma. The changes in pulmonary function test parameters have been consider for evaluation. Methods: This prospective study was undertaken to assess the relative efficiency of budesonide administered from devices like nebulizer, metered dose inhaler and dry powder inhaler in adult patients of chronic stable bronchial asthma. Fifty subjects where administered budesonide (1mg) via nebulizer, budesonide (400 microgram) by metered dose inhaler and dry powder inhaler consecutively each week for four weeks under direct supervision. To analyze the effect of budesonide delivered through different devices pulmonary function test was carried out on the subject before and one hour after administration of the drug on each visit. Results: No significant difference in Peak expiratory flow rate (P=0.77), forced expiratory volume in one second (P=0.851), forced vital capacity (P=0.178) and forced expiratory volume in one second and forced vital capacity ratio (P=0.298) was seen after giving budesonide by different devices. Conclusions: Budesonide delivered by different devices (nebulizer, metered dose inhaler, and dry powder inhaler) have similar effect on lung function in patients of chronic stable bronchial asthma. In the daily clinical practice, the correct choice of an inhaler device should be related with the patient's characteristics. They may be used interchangeably depending on availability, cost and compliance of the patients.